Critical Analyses of International Trade Liberalization and Links Between International Trade and Gender | Análise Crítica da Liberalização do Comércio Internacional e as ligações entre comércio internacional e gênero - Carvalho, Patrícia Nasser de (Mural Internacional, 2020)
Based on a theoretical-exploratory research and focusing on the main arguments of the Trade and Gender Perspectives, this paper explains the different roles of woman in national economies from a critical viewpoint of the liberalization of international trade. It also discusses links between international trade and gender and how women and men are differently impacted by structural and conjuncture circumstances. These differences have defining repercussions to women and gender-differentiated distributional effects in domestic economies and in the global economy in the last four decades, which often reflect in disadvantages for women in the labor market compared with men. Lastly, the paper argues that the so called "feminization" of the workforce, as an important aspect of the globalization process. Countries and economic competition strategies take advantage of structural gender inequalities in countries of the Global South, concentrating investments in low-level tasks and encouraging hiring women in low-paid jobs. Keywords: trade; gender; inequalities. RESUMO Com base em uma pesquisa teórico-exploratória e com foco nos principais argumentos das Perspectivas Comércio e Gênero, este artigo explica os diferentes papeis da mulher nas economias nacionais, tomando um ponto de vista crítico sobre a liberalização do comércio internacional. Ele também discute os vínculos entre comércio internacional e gênero e como mulheres e homens são impactados de maneira diferente pelas circunstâncias estruturais e conjunturais. Essas diferenças têm repercussões definidoras para as mulheres e efeitos distributivos diferenciados por gênero na economia doméstica e global nas últimas quatro décadas, o que geralmente reflete em desvantagens para as mulheres no mercado de trabalho em comparação com os homens. Por fim, o artigo argumenta que a chamada "feminização" da força de trabalho, como um aspecto importante do processo de globalização. Os países e as estratégias de concorrência comercial se aproveitam das desigualdades estruturais entre homens e mulheres nos países do Sul Global, concentrando investimentos em tarefas de baixo nível e incentivando a contratação de mulheres em trabalhos mal remunerados. Palavras-chave: comércio; gênero; desigualdades. Recebido em: 23 jul. 2020 | Aceito em: 17 nov. 2020